IMPLEMENTATION OF BUSINESS TO CUSTOMERS IN ELECTRONIC-CUSTOMER RELATIONSHIP MANAGEMENT TO INCREASE ORDERS FOR ROSE NOODLE PRODUCTS WITH THE WEB - Yunita; Yessica Siagian; Muhammad Ardiansyah Sembiring (Jurnal Teknik Informatika (Jutif), 2022)
Noodles are a food requirement that is a favorite food by the people of Indonesia. Mie Mawar is one of the actors (MSMEs) engaged in the food business that provides yellow noodles or wet noodles without preservatives so that they are healthy for consumption which distinguishes them from other noodle businesses. In the last period, there has been instability in orders for Mie Mawar due to competitors and the marketing process which has been carried out only through word of mouth, so that information dissemination is limited, plus the Covid19. Reports of sales or orders on Mie Mawar still do manual bookkeeping so that it is possible for errors or recording errors to occur and even lose other important transaction files. Therefore Mie Mawar requires Electronic-Customer Relationship (E-CRM) in a strategy to increase the order of Mie Mawar which is more creative to provide solutions to existing problems. The system created will make it easier for customers to process noodle orders more efficiently in order to increase orders and profits for business people. By making three efforts in providing CRM strategies including strategies in Acquiring (Getting customers), Enchancing (Strengthening relationships), and Retaining (Maintaining Customers). With the implementation of E-CRM on Mie Mawar, there was an increase in orders of 51.23% in January 2022. It will continue to increase along with new customers at Mie Mawar.